The Activity of the Chief Executive of a Forensic Organization in the Light of International Standards for Conformity Assessment Requirements - O. A. Surovaya (Теория и практика судебной экспертизы, 2019)
The issues are considered concerning the standardization of forensic activities legal regulation enabling to create an effective transition mechanism to move to a new forensic technological level in our country. The need to implement the international regulations to the national legal system to standardise this activity is highlighted. In forensic activity, it is necessary to apply the new standards for conformity assessment of such principles as the of impartiality and confidentiality. The definitions of these principles are analysed, the conformity assessment requirements for persons involved in conducting forensic investigations are elucidated. The activity of the chief executive of a forensic organization is analysed in the conditions of application the international conformity assessment standards for the mentioned principles as well as his function in managing the institution and personnel.